The Improvement Of Mercury Removal In Natural Gas By Activated Carbon Impregnated With Zinc Chloride - Lisna Rosmayati (Testing Center for Oil and Gas LEMIGAS, 2012)
Natural gas being produced from gas fi elds around Indonesia areas, along with a large number of other harmful substances (CO2,H2S, RSH,COS etc) often contains mercury. Even in small amounts, mercury and its compounds have an extremely harmful effect on human health. Mercury content in the natural gas should be removed to avoid equipment damage in the gas processing plant or the pipeline transmission system from mercury amalgamation and embrittlement of aluminium. Mercury can be removed by using adsorption processes such as activated carbon that is impregnated with chlor, iodine or sulfur. This research is dealing with the process of mercury removal from gas based on principle of adsorption and of chemisorption of mercury by means of activated carbon impregnated with ZnCl2. Time of impregnation is a signifi cant variable that can effect adsorption capacity. The experiment results showed that ZnCl2 impregnation time of 12 hours signifi cantly enhanced the adsorptive capacity for mercury vapour.